Implementation of Hybrid Learning Post Covid-19 Pandemic in Elementary School Level Learning Model - Ari Irawan; Ni Wayan Parwati Septiani; Eddy Saputra; Sutrisno Sutrisno; Rayung Wulan; Mei Lestari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This community service aims to provide assistance to teachers, parents and students regarding hybrid learning. The use of applications to support learning activities while online by using Google class rooms and dojo classes. The method used in this community service activity provides training/workshops and assistance to teachers, parents and students regarding the use of the Google Class Room and Class Dojo applications. The activity stages are divided into four activity stages, namely (1) survey and problem analysis, (2) offered solutions, (3) workshop and mentoring activities, (4) and evaluation. The result of this community service activity is the competence of teachers in using online learning applications such as google class room and closs dojo as media to support hybrid learning. Parents and students can better utilize information and communication technology to carry out remote learning supervision activities.